2013
DOI: 10.1007/s13277-013-1501-9
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 promoter polymorphism (rs3761548) in breast cancer progression: a study from India

Abstract: Breast cancer is the most common female neoplasm that drives the transformation of normal mammary epithelial cells into highly malignant derivatives. Forkhead Box Protein3 (Foxp3), a tumor suppressor/immunomodulatory gene, which controls the function of Treg cells and oncogenes is down regulated in breast cancer. The main aim of the present study is to evaluate the potential influence of Foxp3-3279 C>A polymorphism (rs3761548) and -2383 C>T polymorphism (rs3761549) in 202 breast cancer patients and 130 normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
3
31
1
Order By: Relevance
“…The association between the FOXP3 polymorphism and various cancers has been reported as well for breast cancer [15,16] and hepatocellular carcinoma [17] but this polymorphism has not been reported to confer susceptibility to CRC in a Chinese Han population. Ours is the first to show that a FoxP3 gene polymorphism confers CRC risk and that the AA, AC, and combined A variant genotypes (AA?AC) significantly increased susceptibility to CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the FOXP3 polymorphism and various cancers has been reported as well for breast cancer [15,16] and hepatocellular carcinoma [17] but this polymorphism has not been reported to confer susceptibility to CRC in a Chinese Han population. Ours is the first to show that a FoxP3 gene polymorphism confers CRC risk and that the AA, AC, and combined A variant genotypes (AA?AC) significantly increased susceptibility to CRC.…”
Section: Discussionmentioning
confidence: 99%
“…FOXP3 gene polymorphisms may change Foxp3 functionally or quantitatively, decreasing or eliminating functional Tregs. Also, the FOXP3 polymorphism is associated with autoimmune disease such as allergic rhinitis [12], Graves' disease [13], and psoriasis [14], as well as breast cancer [15,16] and hepatocellular carcinoma [17]. The role of the FOXP3 rs3761548 polymorphism in CRC susceptibility in a Chinese Han population is not certain, so we investigated the association between the FOXP3 rs3761548 polymorphism and the risk of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…These all suggested that a strong activation of oncogenic processes would exist in this lesion. The Foxp3-rs3761548 polymorphisms had been reported to be associated with the risk of various cancers [25,26]. In addition, the Foxp3 gene polymorphisms at rs2280883 and rs3761549 sites may be associated with hepatitis B-related hepatocellular carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of published studies have associated this polymorphism with diseases and other conditions that reflect Treg deficiency, such as allergic rhinitis (325), susceptibility to vitiligo (326), psoriasis (327), some autoimmune diseases (328), non-small-cell lung cancer (329), and breast cancer (330). This association has not been confirmed for other disorders, including endometriosis-associated infertility (319) and systemic sclerosis (331).…”
Section: Foxp3 Mutations and Their Clinical Impactsmentioning
confidence: 99%